Literatur (kepustakaan) keislaman dalam konteks pesantren - Musrifah Musrifah (UIN Sumatera Utara, 2018)
Universally, Islamic literature existing in boarding schools is preserved and passed down from generation to generation directly related to the religious sciences as inherited to Islamic society by past priests in the past called